Validation techniques I: regulatory and statistical background - Tasche, Dirk (Henry Stewart Talks, 2007)
Historical background, New capital standards (Basel II), Requirements on quantitative validation, The binary classification model for rating systems, Bayes' formula, Modeling cyclical effects, Conditional probabilities of default (PD)
Archived at 2022/04/04